Diferentes terapias na osteoartrite induzida por papaína em joelhos de ratos - Rosseto, Laryssa Petrocini [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Due to increasing life expectancy of animals and the growing number of people, osteoarthritis (OA), also known as arthrosis, appears as one of the most important diseases in veterinary and human medicine. Several treatments are use and proposed, but there is no consensus about the best therapy. This study aimed to investigate and compare the efficacy of Low-level laser therapy and therapeutic ultrasound in conjunction with platelet-rich plasma (PRP) in the treatment of osteoarthritis induced in rats’ knees. Randomly were used 72 mice divided into nine groups of eight animals: Control Group (CG), group saline (GCF), Group osteoarthritis 21 days (GOA21), Group osteoarthritis 42 days (GOA42), Group osteoarthritis and Laser (GOALa), Group osteoarthritis and therapeutic Ultrasound (GOAUS), osteoarthritis and PRP Group (GOAPrp), osteoarthritis Group, PRP and Laser (GOAPrpLa) and Group osteoarthritis, PRP and therapeutic ultrasound (GOAPrpUS). It was performed intra-articular infiltration of papain and cysteine 0.03M 4% and 21 days after the induction started three weeks treatment with laser, ultrasound and / or PRP. Evaluations were performed perimeter, thermographic, macro and microscopic. A significant interaction between the groups with respect to time to the perimeter and thermographic ratings, proving that thermography was effective to evaluate the behavior of articular inflammation. Macroscopic changes were observe in the articular cartilage in any animal, a fact confirmed in the histopathological evaluation, which showed up distension and inflammation of the joint capsule, indicating the presence of synovitis. Based on these results it was conclude that the application of a single dose of 4% papain intraarticular is not sufficient to induce osteoarthritis in the knees of mice, but synovitis. In addition, the best results to inflammation of the synovium were using PRP alone or in combination with a laser.

Devido ao aumento da expectativa de vida dos animais e o crescente número de pessoas, a osteoartrite (OA), também conhecida como artrose, surge como uma das afecções mais relevantes na medicina veterinária e humana. Diversos tratamentos são utilizados e propostos, porém não há ainda consenso sobre a melhor terapia. Objetivou-se investigar e comparar a eficácia do Laser de baixa intensidade e o ultrassom terapêutico em conjunto com plasma rico em plaquetas (PRP), no tratamento da osteoartrite induzida em joelhos de ratos. Foram utilizados 72 ratos distribuídos aleatoriamente em nove grupos de oito animais: Grupo Controle (GC), Grupo solução fisiológica (GCF), Grupo osteoartrite 21 dias (GOA21), Grupo osteoartrite 42 dias (GOA42), Grupo osteoartrite e Laser (GOALa), Grupo osteoartrite e Ultrassom terapêutico (GOAUS), Grupo osteoartrite e PRP (GOAPrp), Grupo osteoartrite, PRP e Laser (GOAPrpLa) e Grupo osteoartrite, PRP e ultrassom terapêutico (GOAPrpUS). Foi realizada infiltração intra-articular de papaína 4% e cisteína 0,03M e, 21 dias após a indução, iniciou-se tratamento por três semanas com laser, ultrassom e/ou PRP. Foram realizadas avaliações perimétricas, termográficas, macro e microscópicas. Os resultados mostraram interação significativa entre os grupos em relação ao tempo para as avaliações perimétricas e termográficas, comprovando que a termografia foi eficaz para avaliar o comportamento da inflamação articular. Não foram observadas alterações macroscópicas na cartilagem articular em nenhum animal, fato este confirmado na avaliação histopatológica, onde evidenciou-se distensão e inflamação da cápsula articular, indicando a presença de sinovite. Com base nos resultados foi possível concluir que a aplicação de uma única dose de papaína 4% intra-articular não é suficiente para induzir a osteoartrite em joelhos de ratos, e sim sinovite. Além disso, os melhores resultados obtidos para a inflamação da sinóvia foram com o uso de PRP isolado ou combinado com laser.
Therapies in different osteoarthritis induced papain knees in rats
Keywords: Laser; Synovitis; PRP; Thermography; Therapeutic ultrasound; Laser; Sinovite; PRP; Termografia; Ultrassom terapêutico